The Empowering Disaster Resilient Village Communities (DESTANA) through the Desain of an Early Warning System Based on Renewable Energy and the Internet of Things: Pemberdayaan Masyarakat Desa Tangguh Bencana (DESTANA) dengan Perancangan Alat Early Warning System Berbasis Energi Terbarukan dan Internet of Things - azzududdin, farrel (Jurnal Transformasi Digital Masyarakat (DIGIMAS), 2025)
Gunungsari Village, located in Maesan District, Bondowoso Regency, is an area with several disaster potentials, one of which is a medium-scale flood hazard affecting approximately 2.77 hectares. Flooding frequently occurs due to high rainfall intensity, which causes river water to overflow and inundate residential areas. This disaster often results in significant losses, particularly in infrastructure, with several houses recorded as experiencing minor, moderate, and severe damages. Preventive measures are therefore essential to minimize losses and casualties during such events. The establishment of a Disaster-Resilient Village (DESTANA) and the development of a solar-powered early warning system (EWS) integrated with IoT sensor technology are expected to enhance community preparedness. Residents, especially those organized within DESTANA, participate in training programs on the operation and design of the Smart Early Warning System (Smart EWS). The training includes understanding the working principles of the device, maintenance techniques, and disaster mitigation measures. Through these initiatives, the community is expected to increase awareness of disaster mitigation, thereby improving safety and reducing potential losses during flood events.